Intention of Generation Z to Visit Halal Tourism Destination in West Java - Mutmainah, Lu'liyatul; Andani, Listia; Taufik, Nuryanti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
Indonesia has great potential in the tourism sector, including halal tourism, such as in West Java. Technological developments and digitalization permeating various sectors can influence people's interest in traveling, including Generation Z. This study aims to analyze the factors affecting Generation Z's desire to visit halal tourism destinations in West Java. This study investigates the factors according to the Theory of Perceived Behavior or TPB (subjective norms, attitude towards behavior, and perceived behavioral control), spiritual considerations (religiosity), and digital promotion (electronic word-of-mouth). Furthermore, the study incorporates halal literacy as a moderating variable, assessing its impact on the TPB's influence on tourist intention to visit halal tourism destinations. This study employed an online questionnaire, collecting data from 219 respondents. The gathered data was subsequently analyzed using the Structural Equation Modeling-Partial Least Square (PLS-SEM). The findings reveal that perceived behavioral control, electronic world-of-mouth, and halal literacy have a significant and positive effect on Generation Z's interest in visiting halal tourism destinations in West Java. However, subjective norms, attitudes toward behavior, and religiosity did not have a significant effect. Moreover, halal literacy also failed to moderate the relationship between TPB and behavioral intention in this study. A strategy is needed to develop halal literacy combined with online media tools to promote halal tourism in West Java.